2012
DOI: 10.5402/2012/214362
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Boundary Layer Flow in Porous Medium due to Exponentially Shrinking Permeable Sheet

Abstract: This communication pertains to the study of radiative heat transfer in boundary layer flow over an exponentially shrinking permeable sheet placed at the bottom of fluid saturated porous medium. The porous medium has permeability of specified form. The fluid considered here is Newtonian, without phase change, optically dense, absorbing-emitting radiation but a nonscattering medium. The setup is subjected to suction to contain the vorticity in the boundary layer. The radiative heat flux in the energy equation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Meanwhile, Miklavčič and Wang [3] reported the existence of non-unique solutions for flow over a shrinking sheet. Since then, many studies have considered the effect of several physical parameters such as magnetohydrodynamic (MHD) and radiation on stretching and shrinking surfaces [4][5][6][7][8][9][10][11][12]. The effect of the MHD parameter is an important factor in many industrial and engineering applications, for example, MHD power generators, metallurgical process, crystal growth, metal casting, and cooling of nuclear reactors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Miklavčič and Wang [3] reported the existence of non-unique solutions for flow over a shrinking sheet. Since then, many studies have considered the effect of several physical parameters such as magnetohydrodynamic (MHD) and radiation on stretching and shrinking surfaces [4][5][6][7][8][9][10][11][12]. The effect of the MHD parameter is an important factor in many industrial and engineering applications, for example, MHD power generators, metallurgical process, crystal growth, metal casting, and cooling of nuclear reactors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Case 1: When β → ∞, the momentum equation of the present problem reduces to that of Vyas and Srivastava 4 …”
Section: Mathematical Modelmentioning
confidence: 98%
“…The thermal characteristics of boundary layer flow past stretching/shrinking surfaces have received attention after the pioneer study by Crane 1 . Vyas et al 2–6 reported analysis for flow and heat transfer due to deforming sheet in a porous medium under a variety of assumptions. Wang 7 reported the boundary layer flow over an unsteady shrinking film.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a steady two‐dimensional boundary layer flow of micropolar fluid over an exponentially shrinking sheet is analysed. In real applications, this flow problem may occur in the process of aerodynamic extrusion of plastic sheets, design of chemical processing equipment and field coating for welded pipes ends 41,42 . The flow problem is represented by the Cartesian plane such that the x axis is parallel to the sheet, and the y axis is normal to it, as illustrated in Figure 1.…”
Section: Mathematical Formulationmentioning
confidence: 99%